(untitled) (AYUSHDHARA, 2019)
Undernutrition is a major health problem affects particularly in preschool children (<6 years) with its dire consequences ranging from physical to cognitive growth and susceptibility to infection. Under-nutrition is a condition in which there is inadequate consumption, poor absorption or excessive loss of nutrients. Nutritional supplementation and nutritional interventions are the conventional method for preventing this condition. But even after providing proper nutritional requirements, under weight is getting a serious issue for parents. Kaumarabruthya considered health problems of children are different from adults because of their under developed body (Alpakayatha), immature Dhatus (Aparipakwa Dhatu), less Dosha, Dushya and Mala (Dosha Dushya Mala Alpatha), unstable digestive power (Aniyatha vahni) etc. Jatharagni become very weak in children so they cannot digest and assimilate most of the Guru Aharas. A Dhatu is evolved and transformed into next Dhatu as a result of Pakaprakriya (biotransformation). Vridhi and Kshaya of Dhatu depends on the strength of Jatharagni. If Agni impaired in Dhatus, such evolution cannot take place and leads to the formation of Ama and causing Srothorodha, which results insufficient production of Rasa Dhatu along with other Dhatus chronologically. Parigarbhika, Phakka, Balashosha, Shuska Revati and Karsya are the conditions mentioned in Ayurveda similar to under nutrition. Agnideepana, Pachana, Srotho-sodhana, Samsamana and Laghu Santharpana can be adopted as the line of management in Karsya.